Community Causes of Death in the Central Region of Ghana, the Missing Piece in Mortality Data - Patrick Kafui Akakpo; Emmanuel Gustav Imbeah; Francis Agyarko-Wiredu; Kennedy Awlavi; Kwame Baah-Amoh; Leonard Derkyi-Kwarteng (Hindawi Limited, 2020)
Objective. Mortality data from hospitals in Ghana suggest a changing mortality trend with noncommunicable diseases (cardiovascular disorders) replacing communicable diseases as the leading cause of death. Our objective was to find out the causes of deaths in the communities of the Central Region of Ghana and raise awareness of these causes of deaths while highlighting the differences that exist between data obtained from the community and that obtained from the hospital. Method. Mortality data from Coroner's autopsies mostly provide data about the causes of deaths in the community (out of hospital). A retrospective descriptive study of Coroner's autopsy data at the Cape Coast Teaching Hospital was carried out over a six-year period. The various causes of death were categorized according to broad headings (accidents/injuries/poisoning, cardiovascular, infections, metabolic, neoplasms, and others). Results. A total of 1187 autopsies were reviewed of which 990 (83.4%) were Coroner's cases. Of these Coroner's cases, 719 (72.6%) were male and 271 (27.4%) were female. 521 (52.6%) of victims were young adults (18-44 years), and majority of deaths were unnatural (due to accidents, injuries, and poisoning) (64.1%), followed by the general category of others (15.3%). Cardiovascular deaths (6.6%) were fourth after infections (9.8%). In the leading category, most deaths were due to road traffic accidents (50.4%) as occupants of vehicles and motorcycles (28.7%) and as pedestrians (21.7%). Deaths due to road traffic accidents were followed by deaths due to drowning (14.96%). Conclusion. Although noncommunicable diseases are still the leading causes of death outside the hospital, most of the deaths are due to road traffic accidents and drowning. This is at variance with hospital data that suggest that the leading noncommunicable diseases are cardiovascular disorders and cancer. Again, like data derived from hospitals, infections remain a major cause of death in the Central Region of Ghana. Studies combining the causes of death derived from Coroner's autopsies and communities and from medical certificates of cause of death will present a better picture of the leading causes of death in the Central Region and reveal the true nature of noncommunicable diseases that currently form our largest disease burden.